Fully-weathered granite sedimentary soil roadbed structure and construction method
By using technical means of reinforcement in the fully weathered granite sedimentary soil subgrade structure, the problems of high cost and great environmental impact of the roadbed structure during the rainy season and traditional treatment methods are solved, and the stability and durability of the roadbed are improved.
Patent Information
- Application Number
- CN202411699356.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
AI Technical Summary
The fully weathered granite subgrade structure is prone to collapse during the rainy season, and the traditional subgrade treatment methods are costly and have a great impact on the environment.
The fully weathered granite sedimentary soil subgrade structure is adopted, including the granite sedimentary layer and reinforcement layer. The reinforcement layer is composed of cement, kaolin, lignin, nanosol, polycarboxylic acid water reducing agent and water. Through the laying and rolling of the reinforcement layer, the compactness and compressive strength of the subgrade are enhanced.
It effectively reduces the looseness, crack expansion and collapse caused by weathering of the roadbed structure, improves the stability and durability of the roadbed, and reduces engineering costs and reduces environmental impact.
Smart Images

Figure BDA0005152869380000071 
Figure BDA0005152869380000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of roadbed, and in particular to a fully weathered granite sedimentary soil roadbed structure and a construction method. Background Art
[0002] Alkaline high-quality stones such as limestone are relatively scarce along the road, while acidic stones such as granite are quite abundant. Their poor adhesion to asphalt limits their use. Granite can be used as aggregate for asphalt pavement, which can not only give full play to the good physical and mechanical properties of granite to increase the service life of the pavement, but also solve the problem of shortage of high-quality pavement stones, avoid waste of resources, and reduce the production cost of the project.
[0003] However, granite has strong chemical weathering and deep weathering, and the engineering properties of granite with different weathering degrees vary greatly. The existing fully weathered granite is mainly used as embankment filler. However, fully weathered granite embankments often cause collapse in the rainy season, and as a roadbed, they often cause engineering hazards such as mud bubbling. Traditional roadbed treatment methods, such as replacement and tamping, can improve the stability of the roadbed, but they are costly and have a greater impact on the environment, so their use is limited. Summary of the invention
[0004] In order to improve the instability of the traditional fully weathered granite roadbed structure, the present application provides a fully weathered granite sedimentary soil roadbed structure and a construction method.
[0005] In the first aspect, the present application provides a fully weathered granite sedimentary soil roadbed structure, adopting the following technical scheme: a fully weathered granite sedimentary soil roadbed structure, comprising a granite sedimentary layer and a reinforcement layer, wherein the reinforcement layer comprises the following raw materials in parts by weight: 60-80 parts of cement, 15-30 parts of kaolin, 1-5 parts of lignin, 5-10 parts of nanosol, 5-8 parts of polycarboxylic acid water reducer, and 30-40 parts of water.
[0006] By adopting the above technical solution, a reinforcement layer is laid on the granite sedimentary layer. The cement in the reinforcement layer is combined with kaolin to prepare a reinforcement layer mixture with good strength, which can effectively enter the tiny cracks in the granite sedimentary layer, thereby improving the density and compressive strength of the reinforcement layer and the granite sedimentary layer, and reducing the cracks and loose structure of the roadbed structure caused by granite weathering.
[0007] Lignin can reduce the gaps between cements, improve the hydration reaction of cement, enhance the bonding force of the components of the reinforcement system, improve the crack resistance and durability of the reinforcement layer, and thus reduce roadbed collapse and weathering cracks. Nanosol has good permeability. Nanosol can penetrate from the reinforcement layer into the micro cracks of the granite sediment layer to form a stable nano-scale filling layer, enhance the strength and crack resistance of the reinforcement layer, and at the same time enhance the bonding force between the reinforcement layer and the granite sediment layer, reducing the loose structure, crack expansion, and collapse of the roadbed structure caused by weathering. Polycarboxylic acid water reducer has a good water-reducing effect. Adding it to the reinforcement layer can improve the dispersibility and fluidity of the reinforcement layer mixture, reduce the problem of cracking on the roadbed surface caused by late water volatilization and long-term weathering, and improve the durability of the roadbed structure.
[0008] Preferably, the nano sol is at least one of nano silica sol and nano alumina sol.
[0009] By adopting the above technical scheme, nano silica sol and nano aluminum sol have high reactivity and can react with calcium hydroxide in cement hydration products to generate calcium silicate and calcium aluminate gel, thereby promoting the tight connection of hydration products in the reinforcement layer, reducing the porosity of the reinforcement layer, improving the strength and density of the reinforcement layer, and reducing the problem of loose structure caused by long-term weathering of the road base.
[0010] Preferably, the nanosol is grafted and hybridized with a silane coupling agent, and the grafting and hybridization method comprises the following specific steps: ultrasonically dispersing the nanosol, heating it to 50-70° C., mixing the nanosol with the silane coupling agent, and reacting them at the same temperature to obtain a silane hybrid nanosol.
[0011] By adopting the above technical scheme, the silane coupling agent and the nanosol are grafted and hybridized, which can enhance the steric hindrance between the nanosol particles, reduce the agglomeration of the nanosol, improve the dispersibility of the nanosol, and at the same time promote the nanosol to properly penetrate into the granite sediment layer, enhance the bonding force between the reinforcement layer and the granite sediment layer, enhance the density and strength of the roadbed structure, and reduce the looseness of the roadbed structure and the expansion of cracks.
[0012] Preferably, the granite sediment layer comprises the following raw materials in parts by weight: 80-90 parts of granite residual soil, 5-8 parts of cement, 8-10 parts of sodium hydroxide, 10-20 parts of fly ash, and 5-10 parts of anti-weathering improver.
[0013] By adopting the above technical scheme, adding a proper amount of cement to the granite sedimentary layer, and utilizing the hydration and hydrolysis of cement particles, it is possible to promote ion exchange between granite residual soil and cement hydrates, form organic aggregation, improve the bonding force between cementing particles in the granite sedimentary layer and between particles, enhance the water stability and strength of the granite sedimentary layer, and reduce the phenomenon of roadbed collapse and landslide.
[0014] Sodium hydroxide can react with the minerals of granite residual soil, releasing the silicon and aluminum components in the minerals, and then forming a gelling product when it meets water, which can enhance the adhesion and strength of the granite sedimentary layer system, reduce porosity, and reduce the occurrence of cracks in the roadbed structure. Fly ash has a fine particle size and can fill some pores. After mixing with cement, it will generate flocculent gelling hydration products, enhance the cohesion of granite residual soil, improve the strength and crack resistance of the granite sedimentary layer, and enhance the durability and stability of the roadbed structure.
[0015] Preferably, the anti-weathering improver is an alkaline solution-fiber composite solution, and the mass ratio of the alkaline solution to the fiber is (3-5):1.
[0016] By adopting the above technical solution, the alkaline solution can react chemically with the mineral components in the granite residual soil to form a stable complex, thereby improving the bonding force between the granite residual soil particles, thereby enhancing the structural strength and density of the granite sedimentary layer. The fiber can inhibit the shrinkage and cracking of the granite residual soil during the solidification process, absorb and disperse external force impact in the granite sedimentary layer, improve the crack resistance, compressive strength and impact resistance of the granite sedimentary layer, and enhance the ability of the roadbed to resist external damage.
[0017] Preferably, the alkaline solution is one of polyvinyl alcohol, sodium stearate and sodium silicate, and the fiber is one of basalt fiber, glass fiber and polypropylene fiber.
[0018] By adopting the above technical scheme, polyvinyl alcohol has good bonding and film-forming properties, and can form a continuous polymer network in the granite sediment layer, reducing the phenomenon of easy disintegration of the roadbed structure. Sodium stearate can improve the dispersibility and fluidity of the raw materials of the granite sediment layer, reduce the water-cement ratio, and thus enhance the ability of the granite sediment layer to resist external damage, and improve the strength and impact resistance of the roadbed structure. Sodium silicate can react chemically with the mineral components in the granite residual soil to form a stable silicate complex, improve the bonding force between the granite raw materials, enhance the waterproof performance and density of the granite sediment layer, and thus improve the structural strength and stability of the roadbed structure. Polypropylene fiber has good dispersibility in the granite sediment system, and basalt fiber and glass fiber can play a reinforcing role inside the granite sediment system, improving the strength and impact resistance of the granite sediment layer. Basalt fiber, glass fiber and polypropylene fiber can be dispersed in granite residual soil at different angles, forming a chain network between the fibers, which can limit the space for the movement of granite residual soil, enhance the contact surface and interaction between granite residual soil and fibers, enhance the cohesion between granite residual soil, and thus enhance the ability of granite sedimentary layer to resist external damage.
[0019] In a second aspect, the present application provides a construction method for a fully weathered granite sedimentary soil roadbed structure, using the following technical solution: A construction method for a fully weathered granite sedimentary soil roadbed structure comprises the following specific steps: The granite sediment layer is laid on the bottom layer of the roadbed in advance, and then cement, kaolin, lignin, nanosol, polycarboxylic acid water reducer and water are mixed to form a reinforcement layer mixture, and then the reinforcement layer mixture is laid on the surface of the granite sediment layer, and the surface of the reinforcement layer is rolled until the compaction degree of the reinforcement layer is ≥95%, thus completing the construction of the fully weathered granite sediment soil roadbed structure.
[0020] By adopting the above technical solution, the reinforcement layer is spread on the surface of the granite sediment layer and then rolled in time, which can enable the reinforcement layer mixture to fill into the tiny pores of the granite sediment layer, enhance the bonding force between the reinforcement layer and the granite sediment layer, and improve the density of the reinforcement layer and the granite sediment layer, thereby reducing the phenomenon of crack expansion, loose structure and collapse of the roadbed structure due to long-term weathering.
[0021] Preferably, the granite residual soil is ball-milled in advance, and then an anti-weathering modifier is added and stirred evenly, and then cement, sodium hydroxide and fly ash are added and mixed to obtain a granite mixture, and then the granite mixture is laid on the roadbed surface, and then the laid granite mixture is rolled to obtain a granite sediment layer; Then, cement, kaolin, lignin, nanosol, polycarboxylic acid water reducer and water are mixed to form a reinforcement layer mixture, and then the reinforcement layer mixture is laid on the surface of the granite sedimentary layer, and the surface of the reinforcement layer is rolled until the compaction degree of the reinforcement layer is ≥95%, thus completing the construction of the fully weathered granite sedimentary soil roadbed structure.
[0022] By adopting the above technical solution, the granite residual soil is ball-milled in advance, which can fully activate the granite residual soil and promote the combination of the granite residual soil with other components. Then, the laid granite mixture is rolled to further enhance the density and strength of the granite sedimentary layer and reduce the occurrence of cracks and collapse of the granite sedimentary layer.
[0023] Preferably, the thickness of the granite sedimentary layer is 4-6 cm, and the thickness of the reinforcement layer is 6-8 cm.
[0024] In summary, this application has the following beneficial effects: 1. Since the present application lays a reinforcement layer on the surface of the granite sediment layer, the cement, kaolin, lignin, nanosol, and polycarboxylic acid water reducer in the reinforcement layer are compounded to penetrate into the tiny cracks of the granite sediment layer, thereby enhancing the density and structural strength of the reinforcement layer and the granite sediment layer, and reducing the loose structure, crack expansion, and collapse of the roadbed structure caused by long-term weathering.
[0025] 2. In this application, nano-silica sol and nano-alumina sol are added to the reinforcement layer, which can be closely combined with the hydration products in the reinforcement layer to enhance the density and strength of the reinforcement layer. At the same time, the nano-sol can also penetrate deep into the cracks of the granite sedimentary layer to form a stable nano-scale filling layer, thereby enhancing the structural strength and stability of the reinforcement layer and reducing the loose structure, crack expansion, and collapse of the roadbed structure caused by weathering. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments.
[0027] All raw materials in the examples are commercially available.
[0028] The cement is conventional commercially available silicate cement.
[0029] The nano aluminum sol was purchased from Jiupeng New Materials Nano Aluminum Sol CY-L10B.
[0030] Select PCE-201 as polycarboxylate water reducer. Example
[0031] Example 1 This embodiment provides a fully weathered granite sedimentary soil roadbed structure, a granite sedimentary layer and a reinforcement layer, wherein the reinforcement layer comprises the following raw materials in parts by weight: 70 kg of cement, 23 kg of kaolin, 3 kg of lignin, 8 kg of nanosol, 7 kg of polycarboxylate water reducer, and 35 kg of water. The nanosol is nanosilica sol. The raw material of the granite sedimentary layer is granite residual soil, the nanosol is nanosilica sol, and the average particle size of the nanosilica sol is 10-15 nm.
[0032] The method for preparing a fully weathered granite sedimentary soil roadbed structure comprises the following specific steps: Granite residual soil is laid on the surface of the roadbed, and after rolling, a granite sedimentary layer with an average thickness of 4-6 cm is obtained. Cement, kaolin, lignin, nanosol, polycarboxylic acid water reducer and water are mixed and stirred evenly to form a reinforcement layer mixture. The reinforcement layer mixture is then laid on the surface of the granite sedimentary layer, and the surface of the reinforcement layer is rolled until the compaction degree of the reinforcement layer reaches 95%, and a reinforcement layer with an average thickness of 6-8 cm is obtained, thus completing the construction of the fully weathered granite sedimentary soil roadbed structure.
[0033] Example 2 The difference between Example 2 and Example 1 is that the amount of cement used in the reinforcement layer raw materials is 60 kg, the amount of kaolin used is 15 kg, the amount of lignin used is 5 kg, the amount of nanosol used is 5 kg, the amount of polycarboxylate water reducer used is 8 kg, and the amount of water used is 30 kg.
[0034] Example 3 The difference between Example 3 and Example 1 is that the amount of cement used in the reinforcement layer raw materials is 80 kg, the amount of kaolin used is 30 kg, the amount of lignin used is 1 kg, the amount of nanosol used is 10 kg, the amount of polycarboxylic acid water reducer used is 5 kg, and the amount of water used is 40 kg.
[0035] Example 4 The difference between Example 4 and Example 1 is that the nano sol in the reinforcement layer raw material is nano aluminum sol.
[0036] Example 5 The difference between Example 5 and Example 1 is that the nano-sol in the reinforcement layer raw material is grafted and hybridized by a silane coupling agent, and the silane coupling agent is KH-550.
[0037] The method for preparing a fully weathered granite sedimentary soil roadbed structure comprises the following specific steps: S1: Ultrasonic dispersion of the nanosol, heating to 60° C., mixing the nanosol with a silane coupling agent, and heat-retaining the mixture for 3 hours to obtain a silane hybrid nanosol.
[0038] S2: Lay the granite residual soil on the surface of the roadbed, and after rolling, obtain a granite sediment layer with an average thickness of 4-6 cm, mix cement, kaolin, lignin, silane hybrid nanosol, polycarboxylic acid water reducer and water, stir evenly to form a reinforcement layer mixture, and then lay the reinforcement layer mixture on the surface of the granite sediment layer, and roll the surface of the reinforcement layer until the compaction degree of the reinforcement layer reaches 95%, and obtain a reinforcement layer with an average thickness of 6-8 cm, thus completing the construction of the fully weathered granite sediment soil roadbed structure.
[0039] Example 6 The difference between Example 6 and Example 5 is that the granite sediment layer includes the following raw materials in parts by weight: 85 kg of granite residual soil, 7 kg of cement, 9 kg of sodium hydroxide, and 15 kg of fly ash.
[0040] The method for preparing a fully weathered granite sedimentary soil roadbed structure comprises the following specific steps: S1: Ultrasonic dispersion of the nanosol, heating to 60° C., mixing the nanosol with a silane coupling agent, and heat-retaining the mixture for 3 hours to obtain a silane hybrid nanosol.
[0041] S2: The granite residual soil is ball-milled in advance, and then cement, sodium hydroxide and fly ash are added and mixed, and stirred evenly to obtain a granite mixture, and then the granite mixture is laid on the roadbed surface, and then the laid granite mixture is rolled to obtain a granite sediment layer with an average thickness of 4-6 cm.
[0042] S3: Mix cement, kaolin, lignin, silane hybrid nanosol, polycarboxylate water reducer and water, stir evenly to form a reinforcement layer mixture, then lay the reinforcement layer mixture on the surface of the granite sedimentary layer, and roll the surface of the reinforcement layer until the compaction degree of the reinforcement layer reaches 95%, obtaining a reinforcement layer with an average thickness of 6-8 cm, thus completing the construction of the fully weathered granite sedimentary soil roadbed structure.
[0043] Example 7 The difference between Example 7 and Example 6 is that the granite sediment layer raw material further includes 8 kg of anti-weathering modifier, wherein the anti-weathering modifier is an alkaline solution, and the alkaline solution is a polyvinyl alcohol aqueous solution, and the molecular weight of the polyvinyl alcohol is 250,000.
[0044] S1: Ultrasonic dispersion of the nanosol, heating to 60° C., mixing the nanosol with a silane coupling agent, and heat-retaining the mixture for 3 hours to obtain a silane hybrid nanosol.
[0045] S2: ball-mill the granite residual soil in advance, then add the anti-weathering modifier and stir evenly, then add cement, sodium hydroxide and fly ash and mix evenly to obtain a granite mixture, then lay the granite mixture on the roadbed surface, and then roll the laid granite mixture to obtain a granite sediment layer with an average thickness of 4-6 cm.
[0046] S3: Mix cement, kaolin, lignin, silane hybrid nanosol, polycarboxylate water reducer and water, stir evenly to form a reinforcement layer mixture, then lay the reinforcement layer mixture on the surface of the granite sedimentary layer, and roll the surface of the reinforcement layer until the compaction degree of the reinforcement layer reaches 95%, obtaining a reinforcement layer with an average thickness of 6-8 cm, thus completing the construction of the fully weathered granite sedimentary soil roadbed structure.
[0047] Example 8 The difference between Example 8 and Example 7 is that the amount of granite residual soil used in the granite sedimentary layer raw material is 80 kg, the amount of cement used is 8 kg, the amount of sodium hydroxide used is 10 kg, the amount of fly ash used is 20 kg, and the amount of anti-weathering improver used is 5 kg.
[0048] Example 9 The difference between Example 9 and Example 7 is that the amount of granite residual soil used in the granite sedimentary layer raw material is 90 kg, the amount of cement used is 5 kg, the amount of sodium hydroxide used is 8 kg, the amount of fly ash used is 10 kg, and the amount of anti-weathering improver used is 5 kg.
[0049] Example 10 The difference between Example 10 and Example 7 is that the anti-weathering modifier in the granite sediment layer raw material is an alkaline solution-fiber composite solution, the mass ratio of the alkaline solution to the fiber is 4:1, and the fiber is basalt fiber.
[0050] Embodiment 11 The difference between Example 11 and Example 10 is that the alkaline solution in the granite sediment layer raw material is sodium stearate and the fiber is glass fiber.
[0051] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no nanosol is used in the raw material of the reinforcement layer.
[0052] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that nanosol and kaolin are not used in the raw materials of the reinforcement layer.
[0053] Performance testing According to the fully weathered granite sedimentary soil roadbed structure provided by Examples 1-11 and Comparative Examples 1-2 of the present application, the following performance tests were performed, and the specific test results are shown in Table 1.
[0054] Detection method / test method 1. Strength test With reference to the standard of GB / T17671-1999 "Test method for strength of cement mortar (ISO method)", the flexural and compressive strength of the roadbed structure 28d prepared in this application was tested.
[0055] 2. Disintegration Characteristics The roadbed structure test prepared in this application was placed in a 30°C oven for 2 days, the sample was taken out, weighed and the data was recorded, and then the sample was placed in a disintegrator and fully immersed in water for 60 minutes. The sample was taken out, dried and then baked. This cycle was repeated 3 times, and the disintegration rate was calculated.
[0056] Disintegration rate = (m0-m3) / m0*100%, m0 is the initial mass of the sample, and m3 is the mass of the dried sample after the third disintegration.
[0057] Table 1: Performance test data table It can be seen from the performance test results that the fully weathered granite sedimentary soil roadbed structure prepared in the present application has good strength and density, a reduced disintegration rate, and reduces the phenomenon that the roadbed structure is prone to loose structure, crack expansion, and collapse.
[0058] It can be seen from Examples 1-3 that a reinforcement layer is compounded on the surface of the granite sedimentary layer. From the performance test results, it can be seen that the prepared roadbed structure has a high density and can have good flexural strength and compressive strength. At the same time, the collapse rate is much lower than that of the conventional granite residual soil structure.
[0059] By comparing Example 5 with Example 1, it can be seen that in Example 5, a silane coupling agent is used to modify the nanosol. From the performance test results, it can be seen that the strength of the roadbed structure is further enhanced, which further illustrates that the dispersibility of the nanosol is improved, and it can better penetrate into the granite sediment layer, enhance the density and strength of the roadbed structure, and reduce the looseness of the roadbed structure and the expansion of cracks.
[0060] It can be seen from Examples 7-11 that by mixing granite residual soil with other cement, sodium hydroxide, fly ash, and anti-weathering modifiers in the granite sedimentary layer, the performance test results show that the density and adhesion of the granite sedimentary layer are enhanced, thereby enhancing the strength and structural stability of the roadbed structure.
[0061] By comparing Comparative Examples 1-2 with Example 1, it can be seen that Comparative Example 1 does not use nanosol, and Comparative Example 2 does not use kaolin and nanosol. From the performance test results, it can be seen that the strength of the roadbed structure will decrease. Through the synergistic effect of multiple components, the reinforcement layer mixture can be effectively introduced into the tiny cracks of the granite sedimentary layer, thereby improving the density and strength of the roadbed structure and reducing the phenomenon of loose structure and disintegration.
[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A fully weathered granite sedimentary soil roadbed structure, characterized in that: It comprises a granite sedimentary layer and a reinforcement layer. The reinforcement layer comprises the following raw materials in parts by weight: 60-80 parts of cement, 15-30 parts of kaolin, 1-5 parts of lignin, 5-10 parts of nano sol, 5-8 parts of polycarboxylate water reducer and 30-40 parts of water.
2. The fully weathered granite sedimentary soil roadbed structure according to claim 1 is characterized in that: The nano sol is at least one of nano silica sol and nano aluminum sol.
3. The fully weathered granite sedimentary soil roadbed structure according to claim 2 is characterized in that: The nanosol is grafted and hybridized with a silane coupling agent. The grafting and hybridization method comprises the following specific steps: ultrasonically dispersing the nanosol, heating it to 50-70° C., mixing the nanosol with the silane coupling agent, and reacting them at a temperature-insulating state to obtain a silane hybrid nanosol.
4. The fully weathered granite sedimentary soil roadbed structure according to claim 1, characterized in that: The granite sediment layer comprises the following raw materials in parts by weight: 80-90 parts of granite residual soil, 5-8 parts of cement, 8-10 parts of sodium hydroxide, 10-20 parts of fly ash, and 5-10 parts of anti-weathering improver.
5. The fully weathered granite sedimentary soil roadbed structure according to claim 4, characterized in that: The anti-weathering improver is an alkaline solution-fiber composite solution, and the mass ratio of the alkaline solution to the fiber is (3-5):
1.
6. The fully weathered granite sedimentary soil roadbed structure according to claim 5, characterized in that: The alkaline solution is one of polyvinyl alcohol, sodium stearate and sodium silicate, and the fiber is one of basalt fiber, glass fiber and polypropylene fiber.
7. A construction method for a fully weathered granite sedimentary soil roadbed structure as claimed in any one of claims 1 to 6, characterized in that: The specific steps include: The granite sediment layer is laid on the bottom layer of the roadbed in advance, and then cement, kaolin, lignin, nanosol, polycarboxylic acid water reducer and water are mixed to form a reinforcement layer mixture, which is then laid on the surface of the granite sediment layer and the surface of the reinforcement layer is rolled until the compaction degree of the reinforcement layer is ≥95%, thus completing the construction of the fully weathered granite sedimentary soil roadbed structure.
8. The construction method of the fully weathered granite sedimentary soil roadbed structure according to claim 7 is characterized in that: The granite residual soil is ball-milled in advance, and then an anti-weathering modifier is added and stirred evenly, and then cement, sodium hydroxide and fly ash are added and mixed to obtain a granite mixture, and then the granite mixture is laid on the roadbed surface, and then the laid granite mixture is rolled to obtain a granite sediment layer; Then, cement, kaolin, lignin, nanosol, polycarboxylic acid water reducer and water are mixed to form a reinforcement layer mixture, and then the reinforcement layer mixture is laid on the surface of the granite sedimentary layer, and the surface of the reinforcement layer is rolled until the compaction degree of the reinforcement layer is ≥95%, thus completing the construction of the fully weathered granite sedimentary soil roadbed structure.
9. The construction method of the fully weathered granite sedimentary soil roadbed structure according to claim 7, characterized in that: The thickness of the granite sedimentary layer is 4-6 cm, and the thickness of the reinforcement layer is 6-8 cm.
Citation Information
Cited By
Modified granite weathered material for subbase of expressway and preparation method of modified granite weathered material
CN120535262A